2000
DOI: 10.1002/1439-2054(20000801)280:1<41::aid-mame41>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

The influence of silicate modification and compatibilizers on mechanical properties and morphology of anhydride-cured epoxy nanocomposites

Abstract: IntroductionEpoxy resins are well known as thermally and environmentally stable materials with applications ranging from adhesives to coatings and matrix resins of composites. Anhydride-cured epoxy resins are key components of electrical insulators. Important objective in epoxy resin chemistry is to improve the toughness/stiffness/strength balance without sacrificing processability, dimensional stability and electrical properties. [1] While microfillers are being used extensively to modify epoxy resin properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(57 citation statements)
references
References 12 publications
2
55
0
Order By: Relevance
“…The clay agglomerates and/or non-uniformly distributed clays may present at high clay contents, and these agglomerates can act as crack initiation sites, causing the nanocomposite to fail prematurely at a low failure stress/strain. It was also suggested that different cure speeds between the bulk epoxy and the silicate interfaces may induce internal stresses, leading to a substantial loss of strength [14].…”
Section: Morphologies and Mechanical Properties Of Clay-epoxy Nanocommentioning
confidence: 99%
“…The clay agglomerates and/or non-uniformly distributed clays may present at high clay contents, and these agglomerates can act as crack initiation sites, causing the nanocomposite to fail prematurely at a low failure stress/strain. It was also suggested that different cure speeds between the bulk epoxy and the silicate interfaces may induce internal stresses, leading to a substantial loss of strength [14].…”
Section: Morphologies and Mechanical Properties Of Clay-epoxy Nanocommentioning
confidence: 99%
“…Different cure speeds in the bulk epoxy and at the silicate interface region may also generate significant internal stresses, inducing a loss in strength [11]. Meanwhile, the incorporation of clay could increase the viscosity of the mixture and make the degassing process more difficult, introducing significant amount of nano-or micro-voids.…”
Section: Residual Tensile Properties After Uv Exposurementioning
confidence: 99%
“…Understanding and controlling the various factors that govern the making of exfoliated thermoset/layered silicate nanocomposite is rather complex, several research projects have focused and made contribution to understand some of these issues [4][5][6]. Nanocomposites have the ability and the potential to reduce the permeability of polymer composites against ingress of corrosive substances.…”
Section: Introductionmentioning
confidence: 99%